Pengaruh Kualitas Produk terhadap Keputusan Pembelian: (Studi Kasus di Outlet Dea Cake and Bakery Jalan Veteran Blitar) - Muhamad Adam Badar; Lu' Lu Ul Maknunah; M. Halim Fawazi (Politeknik Kampar, 2025)
This study aims to analyze the influence of product quality on consumer purchasing decisions at the Dea Cake and Bakery outlet located on Jalan Veteran, Blitar. Product quality in this study was measured through several indicators, namely aesthetics, features, performance, durability, and product reliability. This study used a quantitative approach with descriptive methods. Data were obtained by distributing questionnaires to 100 respondents who were consumers of the outlet. The data analysis technique used was simple linear regression analysis to determine the extent of the influence of product quality on purchasing decisions. The results showed that product quality has a positive and significant influence on consumer purchasing decisions. In other words, the better the quality of the product offered, the more likely consumers are to make a purchase. This finding demonstrates the importance of maintaining and improving product quality as a primary strategy in maintaining consumer loyalty and increasing sales volume. Therefore, Dea Cake and Bakery management is advised to continuously evaluate and innovate its product quality to meet consumer expectations and satisfaction on an ongoing basis.